Independent Work as the Highest Form of Educational Activity - Kamalova, Aziza Islomovna (European Journal of Life Safety and Stability (2660-9630), 2023)
this article examines the educational aspects of student independent activity content. It establishes the requirement of taking into consideration student psychological traits connected to age, which serve as the psychological foundation for developing student independent work techniques.